PELAKSANAAN RPJM NAGARI KOTO KACIAK KECAMATAN BONJOL KABUPATEN PASAMAN PROVINSI SUMATERA BARAT (2005-2010) - Izmatul Husna Khutami; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Nagari is a legal public entity that has boundaries with the authority to regulate and manage the interests of local communities based on the origins and customs that recognized and respected in the system of government of the Republic of Indonesia. While the Medium Term Development Plan Nagari (Development Nagari) is a document that shows the direction, goals and policy development Nagari. So the quality of its medium-Nagari becomes very important to note, both in terms of the preparation process, the quality of the document as well as compliance with the legislation in force.The purpose of this study was to determine the Nagari Koto Kaciak Development Plan Implementation and determine whether the implementation of the Development Plan Nagari effective or not.The concept of the theory that I use is the Development Planning and Management Theory government. This type of research is qualitative research with descriptive data assessment. In writing data collection using interview techniques, and documentation.The results of this study indicate that the Development Plan Implementation Nagari Koto Kaciak District of Bonjol ineffective. The problems that occur in the implementation of Nagari Koto RPJM Kaciak is lack of community participation, lack anggaaran, and incompatibility with the implementation of development planning.Keywords: Implementation of Development, RPJM Nagari, Development Planning Theory